MAKESHIFT MARKETS AND POVERTY REDUCTION IN MAKURDI METROPOLIS - Abachi, P. T; Okpe, I. J.; Nomor, D. T (European Scientific Journal, ESJ, 2013)
ï»¿This study was carried out to examine the impact of makeshift trading activities on poverty reduction among participants in Makurdi township of Benue State. The primary data for the study was obtained from structured questionnaire which were distributed to 588 sampled participants in the study area. The data were analyzed using descriptive and Probit Regression Model. The result showed that makeshift trading is an important source of income and employment in Makurdi metropolis. Also, the reasons why these people involve in makeshift trading are to avoid tax, lack of fund to pay for shops in the organized market, and to earn off-work income. We therefore recommend that the state government and the local municipal authority should consider improving on makeshift trading as part of their policies and programs and the participants in the market should evolve into a registered association.